Transformation of the Rural Settlement Network in the Carpathian Region of Ukraine (1989–2020) - Lozynskyy Roman; Zubyk Andriy (European Countryside, 2022)
The article describes research on the Transformation of the Rural Settlement Network in the Carpathian Region of Ukraine in recent decades. The study area covers the Carpathian region of Ukraine, which has the highest share of rural population in the country. The 1989–2020 period was chosen. Quantitative and qualitative methods of analysis of statistical indicators, deductive and inductive methods, and cartographic method were used. The demographic crisis and economic problems of Ukraine did not stop the most important demographic and settlement processes that began in rural settlements of the Carpathian region during the Soviet period. These processes acquired the special features associated with political transition. Depopulation was greatest in the most urbanized Lviv Oblast, especially in the plains, in peripheral villages, where a critical level of negative demographic change had previously been achieved. However, the disappeared villages are few. Population growth in villages in suburban areas of large cities has not stopped. In sparsely urbanized areas, mostly in Transcarpathia and Precarpathia, a large group of villages that have also not been depopulated has emerged. Their development was facilitated by the availability of recreational and forest resources, border location, state support for mountain villages, and some local factors. The real situation in rural Ukraine is partly obscured by imperfect official statistics. In particular, it is difficult to establish population losses due to labor migration abroad.